2015
DOI: 10.1159/000430179
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ferulate Prevents Daunorubicin - Induced Apoptosis in H9c2 Cells via Inhibition of the ERKs Pathway

Abstract: Background: Daunorubicin (DNR)-induced cardiotoxicity, which is closely associated with cardiomyocyte apoptosis, limits the drug's clinical application. The activation of the extracellular regulated protein kinases (ERKs) pathway is responsible for the pro-apoptosis effect of DNR Sodium ferulate (SF) has recently been found to attenuate both DNR-induced cardiotoxicity and mitochondrial apoptosis in juvenile rats. Nonetheless, the precise mechanism underlying SF-induced cardio-protection remains unclear. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Under normal conditions, the anti-apoptotic protein Bcl-2 binds to and sequesters the pro-apoptotic protein Bax. Thus, the ratio of Bax/Bcl-2 plays an important role in determining cell apoptosis or survival [44]. Western blotting of caspase 9, Bcl-2 and Bax, and flow cytometry analysis showed that expression of H7N9/ NS1 activates caspase 9 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Under normal conditions, the anti-apoptotic protein Bcl-2 binds to and sequesters the pro-apoptotic protein Bax. Thus, the ratio of Bax/Bcl-2 plays an important role in determining cell apoptosis or survival [44]. Western blotting of caspase 9, Bcl-2 and Bax, and flow cytometry analysis showed that expression of H7N9/ NS1 activates caspase 9 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although several paradigms, including activation of PKC and ERK [29], inhibition of p38, inhibition of ER stress, decreased apoptosis, necrosis and autophagy, and altered gene expression [25][26][27] have been proposed as putative underlying mechanisms, to date none there has not been a unifying explanation to account for the cellular defects. Furthermore, additional pathways may also play a role in the mediation of the protective effects of FGF-2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that the protective effects of FGF-2 are mediated by PKC and MAPK activation [27]. Moreover, the PI3K/AKT pathway, which is independent of the PKC, PKA, and MAPK signaling pathways [28,29], is activated by FGF-2 and prevents ROS-induced apoptosis in H9c2 cells through the Forkhead box O3 (FoxO3a) transcription factor [30]. The FoxO3a transcription factor is one of the most important downstream targets of PI3K/Akt signaling and a crucial regulator of apoptosis [18,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid is present in Chinese medicinal herbs and exhibit pharmacological activities such antiinflammatory, platelet aggregation inhibitory, antihypertensive and anti-apoptotic effects [179,180]. In a daunorubicin-induced cardiotoxicity model in H9c2 cells, it was observed cellular protection by this compound from the induced apoptosis through a mechanism that involves the interruption of the ERKs signalling pathway [181]. In a scenario of anoxia/reoxygenation injury, where induced intracellular Ca 2+ overload is an important pathophysiological factor, it was observed that sodium ferulate attenuates this increase and improves cell survival in cultured cardiomyocytes through nitric oxide/cGMP-dependent protein kinase (cGMP/PKG) signal pathway [182].…”
Section: Phenolic Acidsmentioning
confidence: 99%